Training Model Development: Transforming a Conservative Da'i to a Moderate by Leveraging Digital Tools - Putra, Robby Aditya; Anrial, Anrial; Fitri, Maulida; Rolando, Dede Mercy (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
This research aims to determine the development of a training model to transform conservative da’i into moderate ones by utilizing digital tools. The research involves a comprehensive analysis of the Da'i's current beliefs and practices, as well as an assessment of the available digital tools that can be utilized to facilitate the transformation process. The results of this research are a training model development that incorporates various digital tools, such as online courses, social media platforms, and digital libraries, to provide the Da'i with a broader understanding of different perspectives and teachings. The potential impact of this study is significant, as it could lead to the development of a more inclusive and progressive religious community. By transforming a conservative Da'i into a moderate one, we can promote understanding, tolerance, and unity among different religious groups. Furthermore, the findings of this study can be applied to other religious contexts, demonstrating the potential of digital tools in promoting religious harmony and understanding. Transforming a conservative Da'i to a moderate by leveraging digital tools requires a comprehensive understanding of the digital landscape, a clear vision for change, and a well-planned and executed digital transformation strategy.